The impact of COVID-19 pandemic on IBD endoscopic procedures in a high-volume IBD Center - Lopetuso, Loris Riccardo; Scaldaferri, Franco; Ianiro, Gianluca; Bibbò, Stefano; Settanni, Carlo Romano; Papa, Alfredo; Armuzzi, Alessandro; Gasbarrini, Antonio; Cammarota, Giovanni (Endoscopy International Open, 2020)
Background and study aims The COVID-19 pandemic is having a major clinical and also organizational impact on national health care systems, particularly in high-volume hospitals that are utilized for several essential clinical needs. We aimed to analyze the short-term impact of the SARS-CoV-2 pandemic on management of endoscopic procedures in patients with inflammatory bowel disease (IBD).Patients and methods This was an observational prospective study exploring major clinical and organizational changes in endoscopic management at the IBD Center – CEMAD of the Fondazione Policlinico Gemelli IRCCS, Rome, Italy since the beginning of SARS-CoV-2 pandemic.Results Our IBD Unit, with up to 1,500 IBD patients receiving biotechnological or experimental therapy, represents a high-volume Italian and European IBD center. Since the beginning of the outbreak, our hospital has been extremely impacted by care related to COVID-19 cases, with a consequent need to dramatically reorganize management of endoscopic procedures for IBD.Conclusions Outbreak restrictions have significantly impacted the volume of endoscopic activities for IBD. Specific strategies have been designed to guarantee a high level of safety for both patients with IBD and healthcare personnel dedicated to their treatment.